Objective Structured Practical Examination as an Assessment Methodology in Human Anatomy Subject: A Practical Implementation Approach; [Examen Práctico Objetivo Estructurado Como Metodología de Evaluación en la Asignatura de Anatomía Humana: Experiencia de Una Implementación Piloto] - Sanchez-Ramirez, C (Universidad de la Frontera, 2024)
Learning in human anatomy has traditionally been assessed by recognizing anatomical structures. Despite their popularity, they can have a subjective component. The Objective Structured Practical Examination (EPOE) has been presented as a more global way of assessment. The aim of this study was to demonstrate the effect on academic performance after the implementation of the EPOE in practical activities. In this study 2312 students were divided into Traditional Methodology (n=1155) and EPOE Methodology (n=1157). In turn, students were identified according to career: Nursing (n=1182), Speech Therapy (n=185), Physical Therapy (n=514), and Occupational Therapy (n=431). Subject conditions were maintained in both groups with three practical evaluations. The grades obtained were analyzed. Assessments 1 and 2 showed no differences between groups. Evaluation 3, which evaluated the nervous system, showed a significant decrease of 0.5 points in the EPOE group. The type of methodology factor was significant in evaluation 3 (p < 0.001; 2p = 0.029) and the average of 3 evaluations (p < 0.029; 2p = 0.002). The career factor was significant for all three evaluations. The interaction of both factors did not show statistical significance. The post hoc analysis showed significant differences between nursing students and the other careers since they obtained better scores in all evaluations (p < 0.05). EPOE methodology did not produce drastic changes in students academic performance and had a broad potential for development due to its non-invasive and non-traumatic comprehensive assessment nature. The nature of the contents should be considered in the design of the teaching-learning methodology and the evaluation methodology, aligning at the micro-curricular level with these fundamental aspects of training new health professionals. © 2024, Universidad de la Frontera. All rights reserved.